Business opportunities arising from cloud computing in information technology industry - Lee, Ho Cheong; Siti Normaziah, Ihsan (Faculty of Computer Systems and Software, 2013)
Nowadays, cloud computing becomes a hot topic not only for information technology (IT) industry but for everyone. Cloud computing does not have a clear definition in the literature yet. Carroll et al. (2012) described cloud computing as a collcomputing concepts that involve a large number of computers that are connected through a real-time communication network (typically the Internet).